Standardisasi dan Uji Aktivitas Antioksidan Ekstrak Bahan Alam Propolis untuk Terapi Infeksi SARS-CoV2 - Diah Kartika Pratami; Yesi Desmiaty; Evita Maria Simorangkir; Deby Faradhila (Fakultas Farmasi Universitas Pancasila, 2021)
Natural ingredients with immunomodulatory, anti-inflammatory, and antioxidant activities can be used as supportive therapy for SARS-CoV2 infection. The aims were standardized the quality and safety of propolis and determined the antioxidant activity of propolis. There are two types of propolis powder samples: microencapsulated propolis powder containing wax (SMPW) and non-waxed (SMP). Standardization includes specific and non-specific parameters. Antioxidant activity test using FRAP and ABTS methods. The total flavonoids of SMPW and SMP were 0.31% and 1.59%. The total phenolic of SMPW and SMP were 83.9082 and 98.0821 mg GAE/g. The losses on drying of SMPW and SMP were 3.65% and 3.88%. The water content of SMPW and SMP were 5.12% and 5.11%. The total ash content of SMPW and SMP were 0.80% and 0.65%. Heavy metal propolis powder negative. ALT and AKK values < 10 CFU/g, microbiology contamination was negative. Antioxidant activity of SMPW with IC50 ABTS 2.4177 ppm and EC50 FRAP 26.41 g/mL. Meanwhile, the antioxidant activity of SMP with IC50 ABTS 2.213 ppm and EC50 FRAP 32.10 g/mL. It was concluded that the extract of propolis met the requirements of the standard for extracts of natural ingredients and had strong antioxidant activity. Propolis powder can be developed for supportive therapy for SARS-CoV2 infection.